Study on Hydrogen Combustion Flame Acceleration Mechanism and Prediction Method During Severe Accidents in Nuclear Power Plants - Ran Liu; Jingyi Yu; Xiaoming Yang; Yong Liu; Rubing Ma; Yidan Yuan (Energies)
Combustion caused by hydrogen-dominated combustible gas mixtures presents critical threats to nuclear safety during severe accidents in nuclear power plants, primarily due to their propensity for flame acceleration, deflagration, and subsequent detonation. Although the direct initiation of detonation from localized hydrogen accumulation at critical concentrations remains challenging, flame acceleration can induce rapid pressure escalation and lead to deflagration-to-detonation transition under suitable conditions. The ultra-high-pressure loads generated almost instantaneously will pose serious risks to containment integrity and equipment or instrument functionality within nuclear facilities. This paper investigates the flame acceleration mechanism and criterion, which is crucial for precise hydrogen risk assessment. A hydrogen combustion flame acceleration model is developed, integrating both laminar and turbulent flame propagation across multiple control volumes. Validated against the RUT test, the model demonstrates high fidelity with a maximum 3.17% deviation in flame propagation velocity and successfully captures the pressure discontinuity. The developed model enables comprehensive simulation with improved predictive accuracy of the flame acceleration process, making it an essential tool for advancing fundamental understanding of hydrogen behavior and severe accident analysis. This model’s development marks a paradigm in nuclear safety research by providing an analytical instrument for integrated severe accident programs in nuclear power plants, contributing to improving the potential hydrogen risks assessment and management in next-generation reactor safety.